The New Translation of ’’The Knight in the Panther Skin’’ - Khatia Mikaberidze (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2026)
On 13th of October 2015 Ivane Javakhishvili Tbilisi State University warmly welcomed Lyn Coffin, a new translator of ''The Knight in the Panther Skin'' from Georgian into English.